Influence of Cattle Trails on Runoff Quantity and Quality. Issue 2 (1st March 2017) - Miller, Jim J.; Curtis, Tony; Chanasyk, David S.; Willms, Walter D.
Abstract : Cattle trails in grazed pastures close to rivers may adversely affect surface water quality of the adjacent river by directing runoff to it. The objective of this 3‐yr study (2013–2015) in southern Alberta, Canada, was to determine if cattle trails significantly increased the risk of runoff and contaminants (sediment, nutrients) compared with the adjacent grazed pasture (control). A portable rainfall simulator was used to generate artificial rainfall (140 mm h −1 ) and runoff. The runoff properties measured were time to runoff and initial abstraction (infiltration), total runoff depth and average runoff rates, as well as concentrations and mass loads of sediment, N, and P fractions. Cattle trails significantly ( P ≤ 0.10) decreased time to runoff and initial abstraction (26–32%) in the 2 yr measured and increased total runoff depth, runoff coefficients, and average runoff rates (21–51%) in 2 of 3 yr. Concentrations of sediment, N, and P fractions in runoff were not significantly greater for cattle trails than for control areas. However, mass loads of total suspended solids (57–85% increase), NH4 –N (31–90%), and dissolved reactive P (DRP) (30–92%) were significantly greater because of increased runoff volumes. Overall, runoff quantity and loads of sediment, NH4 –N, and DRP were greater for cattle trails compared with the adjacent grazed pasture, and hydrologic connection with cattle‐access sites on the riverbank suggests that this could adversely affect water quality in the adjacent river. Extrapolation of the study results should be tempered by the specific conditions represented by this rainfall simulation study. Core Ideas: Runoff quantity was significantly increased in cattle trails compared with adjacent grazed pasture. Cattle trails did not increase contaminant concentrations in runoff. Mass loads of TSS, NH4 –N, and DRP were significantly greater because of increased runoff volumes. Field observations revealed a hydrologic link between cattle trails and river. Runoff in cattle trails may adversely impact water quality in adjacent rivers.